Analysis of the Implementation of Abandon ship drill to Face Emergency Situations on the MV Pacific Bulk Ship - Mochammad Anggit Satria Yudha; AA Istri Sri Wahyuni; Otri Wani Sihaloho; Arleiny (International Journal of Science and Environment (IJSE), 2026)
Abandon ship drill is a mandatory safety exercise conducted on board a ship to improve crew readiness in facing emergencies according to SOLAS 1974 Chapter III Regulation 19. A common problem is that the exercise implementation has not been optimal, especially related to the understanding of tasks based on the muster list, the readiness of safety equipment, and crew coordination. This study aims to analyze the implementation of abandon ship drill and assess the level of readiness and understanding of crew on MV. Pacific Bulk in facing emergencies. The study used a qualitative method with the Miles and Huberman analysis model which includes data reduction, data presentation, and drawing conclusions. Data were obtained through observations during sea practice, interviews with officers and crew, and documentation of drill activities. The results of the study indicate that the abandon ship drill has been carried out routinely every month and follows basic safety procedures such as sounding the emergency alarm, gathering the crew at the muster station, and briefings from the captain. However, the implementation has not been fully optimal because the lifeboat during the exercise was only lowered to the embarkation deck and there were still delays in crew, uneven understanding of tasks, and less than optimal post-drill evaluation. Therefore, it is necessary to increase crew familiarization, implement more disciplined and sustainable training, and conduct a comprehensive evaluation after the drill as a preventive measure to improve crew readiness.